Colossus : The Price of America's Empire - Ferguson, Niall (London Penguin Books, 2005)
Is America the new world empire? Presidents from Lincoln to Bush may have denied it but, this book shows, the US is in many ways the greatest imperial power of all time. This title reveals, is an empire running on empty, weakened by chronic defecits of money, manpower and political will.
Include Index, Bibliography and Notes
Keywords: United States -- Diplomatic relations -- Imperialism